2020
DOI: 10.1021/acsami.0c04987
|View full text |Cite
|
Sign up to set email alerts
|

Hot Carriers and Photothermal Effects of Monolayer MoOx for Promoting Sulfite Oxidase Mimetic Activity

Abstract: Local surface plasmon resonance (LSPR)-enhanced catalysis has brought a substantial amount of opportunities across various disciplines such as photocatalysis, photodetection, and photothermal therapeutics. Plasmon-induced photothermal and hot carriers effects have also been utilized to activate the enzyme-like reactions. Compared with natural enzymes, the relatively low catalytic performance of nanozymes severely hampered the potential applications in the field of biomedicine. For these issues mentioned above,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 70 publications
1
9
0
Order By: Relevance
“…The lower K m and higher V max imply that MoS 2 /BPE possesses more superior SuO x mimic activity over MoS 2 . 55,56 The activity of MoS 2 /BPE is comparable to that of the recently reported artificial SuO x (Table S3). As for MoS 2 / BPE, the stability of SuO x mimic catalysis is also significant for future applications.…”
Section: ■ Experimental Sectionsupporting
confidence: 81%
See 1 more Smart Citation
“…The lower K m and higher V max imply that MoS 2 /BPE possesses more superior SuO x mimic activity over MoS 2 . 55,56 The activity of MoS 2 /BPE is comparable to that of the recently reported artificial SuO x (Table S3). As for MoS 2 / BPE, the stability of SuO x mimic catalysis is also significant for future applications.…”
Section: ■ Experimental Sectionsupporting
confidence: 81%
“…In SuO x mimic catalysis, SO 3 2– is absorbed by MoS 2 and forms *SO 3 2– at first, which is oxidized to *SO 4 2– in turn. Finally, • SO 4 – desorbs from the MoS 2 surface . For MoS 2 /BPE and MoS 2 , SO 3 2– absorption and *SO 3 2– oxidation are both thermodynamically favorable downhill processes (Figure a and Scheme S2).…”
Section: Resultsmentioning
confidence: 98%
“…greatly enhanced upon LSPR excitation [130] due to the hot carriers and photothermal effects. The results confirmed the existence of oxygen vacancies, which boosted the carrier intensity of ML-MoO x .…”
Section: Plasmonic Non-metal-based Pnzymesmentioning
confidence: 99%
“…Similarly, Wan et al reported that the CAT-like activity of Pt could be enhanced by the photothermal effect from plasmonic hollow AuAg nanocages (Figure 5C). [127] Moreover, Yang et al reported that the photothermal effect of monolayer MoO x promoted the sulfite oxidase (SuO x ) mimetic activity, [130] and Zhang et al proposed that platinum-doped prussian blue (PB) nanozyme exhibited the tunable LSPR frequency with significantly improved photothermal conversion efficiency, which could be used for enhancing the antioxidative catalytic activity of nanozyme. [53] Noteworthy, when leveraging the photothermal effect of a PNP to regulate the enzyme-mimicking activity, the morphological changes of PNzymes upon continuous laser irradiation are rarely explored.…”
Section: Photothermal Effectmentioning
confidence: 99%
See 1 more Smart Citation